2015
DOI: 10.3889/oamjms.2015.051
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns of Children with Autism Spectrum Disorder: A Study Based in Egypt

Abstract: AIM:In the hope to assist in tailoring individualized nutritional therapy, this study aimed to assess the nutritional status of autistic children.MATERIAL AND METHODS:This cross-sectional study included 80 autistic children, divided into two groups: group 1 (aged 3- 5 years) and group 2 (aged 6-9 years). Diagnosis was performed based on the criteria for autistic disorder as defined in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Autism Diagnostic Interview Revised and Autism Ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
1
10
1
3
Order By: Relevance
“…Previous researchers [ 4 ] [ 39 ] [ 40 ] [ 41 ] [ 42 ] showed that autistic children are very sensitive to bitter taste leading to refusal of certain foods and it could be the potential reason for reduced intake of vegetables in par with our study where 68.9% of the children rejected having vegetables. In contrast, According to Diolordi L et al, [ 39 ] fruits are preferred by the autistic children may be because of its texture and sweet taste wherein our study, 78.7% of the children preferred having fruits.…”
Section: Discussionsupporting
confidence: 67%
“…Previous researchers [ 4 ] [ 39 ] [ 40 ] [ 41 ] [ 42 ] showed that autistic children are very sensitive to bitter taste leading to refusal of certain foods and it could be the potential reason for reduced intake of vegetables in par with our study where 68.9% of the children rejected having vegetables. In contrast, According to Diolordi L et al, [ 39 ] fruits are preferred by the autistic children may be because of its texture and sweet taste wherein our study, 78.7% of the children preferred having fruits.…”
Section: Discussionsupporting
confidence: 67%
“…These findings are supported by previous studies. First, individuals with ASD often have eating problems, such as food selectivity and specialized dietary habits, which make healthy dietary interventions less effective 38,39 . Second, individuals with ASD spend less time on physical activities and more time on sedentary activities 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Current nutritional studies in the ASD population mainly concern children, and dietary intervention studies on patients with autism are very rarely performed in adulthood. It was reported that inadequate intake of some micronutrients are highly significant especially in individuals at older age, when the risk of developing diet-related diseases such as obesity and cardiovascular disease is much higher than in childhood [ 18 , 26 ]. However, research on nutrition, diets and their effects on the older group of people with ASD is still rare.…”
Section: Introductionmentioning
confidence: 99%